2011
DOI: 10.1108/17579861111108644
|View full text |Cite
|
Sign up to set email alerts
|

Laser shock processing with two different laser sources on 2050‐T8 aluminum alloy

Abstract: PurposeThe purpose of this paper is to conduct a comparative study of the surface modifications induced by two different lasers on a 2050‐T8 aluminum alloy, with a specific consideration of residual stress and work‐hardening levels.Design/methodology/approachTwo lasers have been used for Laser shock peening (LSP) treatment in water‐confined regime: a Continuum Powerlite Plus laser, operating at 0.532 mm with 9 ns laser pulses, and near 1.5mm spot diameters; a new generation Gaia‐R Thales laser delivering 10 J‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
2
7
0
4
Order By: Relevance
“…Differences between the magnitude of the residual stress after LSP in the x-direction (s x ) and in the y-direction (s y ) in the surface region are found in multitude of Refs. [12][13][14][15], but until now the explanation for this residual stress anisotropy has been an open question [8]. Trdan et al [16] (in which residual stress evaluation also confirmed beneficial compressive residual stresses after LSPwC, with higher compressive residual stress in the advancing LSPwC) studied the LSPwC effects on the dislocation generation, dislocation transition and grain refinement through-depth distribution, which could be related to the residual stress anisotropy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differences between the magnitude of the residual stress after LSP in the x-direction (s x ) and in the y-direction (s y ) in the surface region are found in multitude of Refs. [12][13][14][15], but until now the explanation for this residual stress anisotropy has been an open question [8]. Trdan et al [16] (in which residual stress evaluation also confirmed beneficial compressive residual stresses after LSPwC, with higher compressive residual stress in the advancing LSPwC) studied the LSPwC effects on the dislocation generation, dislocation transition and grain refinement through-depth distribution, which could be related to the residual stress anisotropy.…”
Section: Introductionmentioning
confidence: 94%
“…[13]) as a quasi-Gaussian function: P(x,y,t)¼P(t)exp[À 0.85(x 2 þy 2 )/R 2 ], where x and y are the surface coordinates and R is the pulse radius. In addition, when simulating a large number of LSPwC pulses applied at different locations and times, a minimum time interval between successive impacts had to be selected to ensure a quasi-residual stress field (shock and relaxation).…”
Section: Shock Wave Modeling: Evolution and Spatial Distributionmentioning
confidence: 99%
“…Considering Eqs (7), (9) and (11) in Eq. (12), the residual fatigue life for damaged specimen can be calculated by…”
Section: Dissipated Energy Enhancement Mechanismmentioning
confidence: 99%
“…found that the increase in hardness is slightly because of hardening effects and can be mainly attributed to the presence of compressive residual stresses. Peyre et al . treated a 2050‐T8 aluminium alloy by two different lasers (3 and 1.5 J output energies) and found that similar surface deformations and work‐hardening levels were observed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation